Special features of the heading complex in the novel “Imaginary Interlocutor” by O. Savych - Рубан, Алла Анатоліївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article presents an analysis of the heading complex in the novel by I. Savych “Imaginary Interlocutor”. The author of the article analyses and classifies the headings of the novel: the general title and the titles of its eighteen chapters. The main principle of the classification is correlated with the traditional components of the text: thematic content, problems, plot, character system, details, time and space, etc. under analysis is also “the energy” of the headings: connection of the whole novel and its chapters with other works of Russian and foreign literature of different times.The other aspect of the analysis of the novel discussed is epigraph which functions in several coupling systems: with the novel context, with the text of the novel and its chapters, with different epigraphs. The author of the research considers communicative types and functions (informative and form-meaning ones) of epigraphs in literary interpretation. In O. Savych’s novel meaningful information of the epigraph is a prospective message concerning thematic, plot and conceptual moments of the book. Special attention is paid to the form-building function in the text. Types of the epigraphs in the novel are different according to the source. Epigraph, as an element of O. Savych’s text is multifunctional. Its main and universal function is dialogical: epigraph is one of ways to make a monologue dialogical, to present a different from the author’s point of view. Thus, the system of the author’s thought, their literary orientation are revealed. While the division of the novel into 18 chapters gives to the novel the character of completeness, enhances its inner unity, epigraphs outline the open character of the text borders.The analysis of the heading complex allows to make some conclusions about the nature of O. Savych’s book and its place in Russian literature of 1920 – 1930 years.